PENGARUH KOMUNIKASI DAN KERJA SAMA TIM TERHADAP KINERJA KARYAWAN (Studi Kasus pada Bagian Housekeeping PT. Resik Gunamaju) - Luthfia Putri Aulia; Haidilia Maharani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study is to determine the effect of communication and teamwork on employee performance in the housekeeping department of PT Resik Gunamaju. This research uses a quantitative method and employs primary and secondary data. Probability sampling is used with the Slovin formula in determining the sample size of 66 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study show that partially there is a positive and significant effect of communication on employee performance, with a calculated t-value (4.740) > t-table (1.998) and a significance value (0.000) < (0.050), thus H0 is rejected and Ha is accepted. Partially, there is a positive and significant effect of teamwork on employee performance, with a calculated t-value (3.686) > t-table (1.998) and a significance value (0.000) < (0.050), thus H0 is rejected and Ha is accepted. Communication and teamwork simultaneously have a significant effect on employee performance with the regression equation Y = 15.360 + 0.396X1 + 0.165X2, constant 15.360, coefficient X1 0.510 and coefficient X2 0.418, while the correlation value or r is 0.538 and the coefficient of determination value is 0.290 or 29.0%, while the remaining 71.0% is influenced by other factors, with a calculated F-value (12.846) > F-table (3.140), and a significance value (0.000) < (0.050). Thus H0 is rejected and Ha is accepted, this indicates that there is a positive and significant effect of communication and teamwork on employee performance in the Housekeeping Department of PT Resik Gunamaju.